2013
DOI: 10.1111/jnp.12034
|View full text |Cite
|
Sign up to set email alerts
|

Conscious and unconscious processing of facial expressions: Evidence from two split‐brain patients

Abstract: We investigated how the brain's hemispheres process explicit and implicit facial expressions in two 'split-brain' patients (one with a complete and one with a partial anterior resection). Photographs of faces expressing positive, negative or neutral emotions were shown either centrally or bilaterally. The task consisted in judging the friendliness of each person in the photographs. Half of the photograph stimuli were 'hybrid faces', that is an amalgamation of filtered images which contained emotional informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 66 publications
6
44
5
Order By: Relevance
“…), and participants were asked to rate 'friendliness' of single chimeric faces, assuming that happy facial expressions were judged as more friendly than angry looking faces, especially when happy face expressions were displayed on the left of the chimeric face. However, in contrast to broadband face stimuli which showed significant modulation in friendliness ratings, depending on the face expression being happy, neutral or angry, Prete, D'Ascenzo et al (2015) found no modulation in friendliness ratings for hybrid stimuli. All friendliness ratings for hybrid stimuli were numerically slightly below the score of 3 ("neutrality point"), suggesting that participants were unable to detect the emotion in hybrid stimuli.…”
Section: Discussioncontrasting
confidence: 78%
“…), and participants were asked to rate 'friendliness' of single chimeric faces, assuming that happy facial expressions were judged as more friendly than angry looking faces, especially when happy face expressions were displayed on the left of the chimeric face. However, in contrast to broadband face stimuli which showed significant modulation in friendliness ratings, depending on the face expression being happy, neutral or angry, Prete, D'Ascenzo et al (2015) found no modulation in friendliness ratings for hybrid stimuli. All friendliness ratings for hybrid stimuli were numerically slightly below the score of 3 ("neutrality point"), suggesting that participants were unable to detect the emotion in hybrid stimuli.…”
Section: Discussioncontrasting
confidence: 78%
“…The present behavioural results strongly confirm those previously obtained by means of hybrid faces (Laeng et al ., ; Leknes et al ., ; Prete et al ., , ,b), showing that the low‐passed emotional core of these stimuli is sufficient to modulate participants’ responses according to their content and in a subliminal fashion. Of central interest in this regard is the difference between behavioural and ERP evidence regarding fear expression; the emotional LSF of hybrid afraid faces did not modulate participants’ responses, which were undistinguishable from those given to neutral faces.…”
Section: Discussionmentioning
confidence: 98%
“…In the same way, in this study we tested the usefulness of hybrid faces by presenting three emotional expressions (in addition to the neutral expression), but a study considering all of the six basic emotions could be more exhaustive for validating this paradigm as a possible tool. Similarly, we implemented the paradigm by using the same spatial filter for all emotions, because previous studies showed an effect on the friendliness evaluations by means of these stimuli (Laeng et al ., ; Leknes et al ., ; Prete et al ., , ,b). However, as reported above, Smith & Schyns () demonstrated that different emotions can be optimally detected as a function of filtering at different spatial frequencies, happiness being better detected based on the LSF, and anger and fear being better detected based on the high spatial frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, the short stimulus exposure used in the divided visual field paradigm (tachistoscopic presentation), together with the lateralized presentation of the stimuli (eccentricity), may facilitate the low spatial frequency analysis and thus the right-hemispheric processing. The same right-hemispheric superiority for low spatial frequencies has been confirmed also by means of complex visual stimuli, both in healthy participants and in split-brain patients (e.g., [26][27][28]). Nevertheless, in the same study Wilkinson and Halligan [24] failed to find a cerebral imbalance in the detection of symmetry when "double axes stimuli" (squares in which a circle could be placed on-center or off-center) were presented, explaining this finding as possibly attributable to the fact that square bisection activates bilateral networks.…”
Section: Introductionmentioning
confidence: 53%